Nitrification of Fish Processing Waste Water using Mixed Cultures of Nitrosomonas and Nitrobactor for Ammonia Degradation (Phase-I) (Global Journal of Science Frontier Research, 2014)
The present study aims at nitrification of fish processing wastewater using mixed cultures of nitrifying bacteria, Nitrosomonas and Nitrobactor. Parameter optimization of the process is done by using Response Surface Methodology (RSM). Central-Composite design is used to optimize the various parameters for nitrifying cultures. The process parameters namely, the pH, temperature, microbial load and effluent concentration are optimized. Optimized values are obtained from the second order polynomial equation that resulted from the Central-Composite design. The physical -chemical characteristics of fish processing wastewater are presented. Their values show the alkaline nature and high levels of COD and BOD values. The capability of the various models, namely, Logistic, Monod, Herbert, Shehata & Marr, Tessier and Haldane models in representing the batch kinetic data of the present work are reported for mixed nitrifying cultures, while Logistic model is best suited in describing the nitrification of the fish processing waste water. Experimental data collected in a Rotating Biological Contactor using mixed culture, operated on a batch basis for twenty two days with an average organic loading rate of 150 mg/L of ammonia at 20 rpm are reported for every twenty four hours. The future research is proposed for the nitrification of waste water using isolated nitrifying organism from soil for ammonia degradation.
Keywords: nitrification; fish processing waste water; ammonia degradation; nitrosomonas; nitrobactor